AN EVALUATION OF SUPPLY CHAIN RESILIENCE STRATEGIES IN RESPONDING TO GLOBAL DISRUPTIONS IN THE MANUFACTURING AND DISTRIBUTION SECTORS - Hery Purnomo; Subagyo; Faisol; Badrus Zaman; Poniran Yudho Leksono (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Global disruptions such as the COVID-19 pandemic, geopolitical conflicts and logistics crises have caused significant disruption to industrial supply chains and global distribution. This study aims to evaluate supply chain resilience strategies in the face of global disruptions in the industrial and distribution sectors using a literature review approach. The research findings indicate that supply chain resilience comprises four key dimensions: robustness, flexibility, agility, and redundancy, with determining factors including digital capability, supply chain visibility, collaboration, supplier diversification, and government policy support. Evaluation strategies encompass redundancy, operational flexibility, digitalisation, collaboration, and regionalisation, with performance indicators including time to recover, fill rate, service level, cost efficiency, and supply continuity. The manufacturing sector requires capacity redundancy and flexible production, whilst the distribution sector requires routing flexibility and transport optimisation. Companies implementing adaptive strategies experienced a 30% reduction in disruption impacts, with supplier diversification reducing disruption time by 25% and digital adoption improving demand forecasting by 35%. Practical implications provide guidance for practitioners in developing adaptive strategies, with recommendations for further research focusing on AI-blockchain integration, green resilient supply chains, and standardised resilience indicators.